Silent uterine perforation by an IUCD inserted during the puerperium. (20th July 2011) - Harvey, Hugh; Richenberg, Jonathan
Abstract : A 38-year-old lady, with a history of recent caesarean section, was diagnosed with a silent uterine perforation by a copper intrauterine contraceptive device under fluoroscopic examination. The incidence of uterine perforation and the increased risk in the puerperium are discussed. The use of ultrasound as the first line investigation is recommended.